Factors Affecting the Adoption and Implementation of ISO 14001/EMS in Oman: A Study of SME Sectors - Chinnasamy, Gopalakrishnan; Srivastava, Preeti; Soundararajan, Gopalakrishnan; AL-Saidy, Fahad Nasser Humaid (Asian Journal of Empirical Research, 2017)
This study intends to observe and examine the various external and internal influences, which are affecting the small to medium-sized enterprises (SMEs) in Oman to accept ISO14001 or reject Environment Management System (EMS). The concept of implementing quality accreditation by small firms is relatively small as compared to bigger firms. Market in general is cynical about the long-term benefits of this quality certification in relation with the costs incurred by the SMEs. The SMEs in Oman are typically focused on a few sectors namely transportation, chemicals, construction, automobile, manufacturing, storage, textiles and food & beverage. This research is an effort to identify and provide solutions and recommendations for successful implementation of ISO 14001 for Omani SMEs.